The impact of social media promotion with infographics and podcasts on research dissemination and readership. Issue 2 (13th September 2017) - Thoma, Brent; Murray, Heather; Huang, Simon York Ming; Milne, William Ken; Martin, Lynsey J.; Bond, Christopher M.; Mohindra, Rohit; Chin, Alvin; Yeh, Calvin H.; Sanderson, William B.; Chan, Teresa M.
Abstract: Objective: In 2015 and 2016, the Canadian Journal of Emergency Medicine (CJEM) Social Media (SoMe) Team collaborated with established medical websites to promote CJEM articles using podcasts and infographics while tracking dissemination and readership. Methods: CJEM publications in the "Original Research" and "State of the Art" sections were selected by the SoMe Team for podcast and infographic promotion based on their perceived interest to emergency physicians. A control group was composed retrospectively of articles from the 2015 and 2016 issues with the highest Altmetric score that received standard Facebook and Twitter promotions. Studies on SoMe topics were excluded. Dissemination was quantified by January 1, 2017 Altmetric scores. Readership was measured by abstract and full-text views over a 3-month period. The number needed to view (NNV) was calculated by dividing abstract views by full-text views. Results: Twenty-nine of 88 articles that met inclusion were included in the podcast (6), infographic (11), and control (12) groups. Descriptive statistics (mean, 95% confidence interval) were calculated for podcast (Altmetric: 61, 42-80; Abstract: 1795, 1135-2455; Full-text: 431, 0-1031), infographic (Altmetric: 31.5, 19-43; Abstract: 590, 361-819; Full-text: 65, 33-98), and control (Altmetric: 12, 8-15; Abstract: 257, 159-354; Full-Text: 73, 38-109) articles. The NNV was 4.2 for podcast, 9.0 for infographic, and 3.5 for control articles. Discussion: Limitations included selection bias, the influence of SoMe promotion on the Altmetric scores, and a lack of generalizability to other journals. Conclusion: Collaboration with established SoMe websites using podcasts and infographics was associated with increased Altmetric scores and abstract views but not full-text article views. RÉSUMÉ: Contexte: En 2015-2016, l'équipe des médias sociaux du Journal canadien de la médecine d'urgence a travaillé en collaboration avec des équipes de sites Web médicaux établis afin de faire la promotion d'articles du Journal par la baladodiffusion et l'infographie, et de suivre l'évolution de la diffusion et du lectorat. Méthode: Le choix des articles du Journal, parus dans les sections Original Research et State of the Art en vue de la promotion par la baladodiffusion et l'infographie a été effectué par l'équipe des médias sociaux d'après sa perception de l'intérêt pour les médecins d'urgence. Un groupe témoin d'articles parus dans les numéros de 2015 et de 2016 et ayant fait l'objet de la promotion habituelle dans Facebook and Twitter a été constitué de manière rétrospective à l'aide des scores Altmetric les plus élevés. Les études portant sur des sujets liés aux médias sociaux ont été écartées. En ce qui concerne la diffusion, elle a été quantifiée selon les scores Altmetric en date du 1 er janvier 2017. Quant au lectorat, il a été mesuré à l'aide du nombre de visionnements de résumés ou d'articles en version intégrale sur une période de 3 mois. Le nombre requis de visionnements (NRV) a été calculé par la division du nombre de visionnements de résumés par celui d'articles en version intégrale. Résultats: Sur 88 articles qui respectaient les critères d'inclusion, 29 ont été répartis comme suit : 6 dans le groupe de la baladodiffusion, 11 dans celui de l'infographie et 12 dans le groupe témoin. Des statistiques descriptives (moyenne : IC à 95 %) ont été calculées pour la baladodiffusion (score Altmetric : 61→42-80; résumé : 1795→1135-2455; texte en version intégrale : 431→0-1031), pour l'infographie (score Altmetric : 31, 5→19-43; résumé : 590→361-819; texte en version intégrale : 65→33-98) et pour les articles témoins (score Altmetric : 12→8-15; résumé : 257→159-354; texte en version intégrale : 73→38-109). Le NRV a atteint 4, 2 pour la baladodiffusion; 9, 0 pour l'infographie et 3, 5 pour les articles témoins. Discussion: Les points faibles comprenaient un biais de sélection, l'influence de la promotion des médias sociaux sur les scores Altmetric et le manque de généralisation à d'autres revues. Conclusion: La collaboration avec des équipes de sites Web de médias sociaux à l'aide de la baladodiffusion et de l'infographie a été associée à une augmentation des scores Altmetric ainsi que du nombre de visionnements des résumés mais pas à une augmentation du nombre de visionnements des articles en version intégrale.